HUBUNGAN DUKUNGAN KELUARGA TERHADAP EFIKASI DIRI IBU MENYUSUI DALAM MEMBERIKAN ASI EKSKLUSIF - Dian Vitasari; Febriana Sabrian; Juniar Ernawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Exclusive breastfeeding role to optimize growth and development of infant. Breastfeeding mothers require breastfeeding self-efficacy which refers to the mother's confidence in the ability to breastfeed her infant. Mothers need family support to increase breastfeeding self- efficacy. The aim of this research was to identify the relationship between family support with the breastfeeding self-efficacy of mother in giving exclusive breastfeeding. The design was descriptive correlational research with cross sectional approach. The samples were 80 breastfeeding mothers with infants aged 0-6 months using purposive sampling. This research used questionnaire that already tested for validity and reliability. This research using univariate and bivariate analysis with chi-square test. The result showed that p value was 0.000 (p value <0,05), accordingly it can be concluded that there is relation of family support to breastfeeding self efficacy of mother in giving exclusive breastfeeding. This study finds that providing families support for mothers to succeed in providing exclusive breastfeeding.  Keywords:  Breastfeeding self-efficacy, Family support